Bio‐Inspired Motion Mechanisms: Computational Design and Material Programming of Self‐Adjusting 4D‐Printed Wearable Systems. Issue 13 (14th May 2021) - Cheng, Tiffany; Thielen, Marc; Poppinga, Simon; Tahouni, Yasaman; Wood, Dylan; Steinberg, Thorsten; Menges, Achim; Speck, Thomas
Abstract: This paper presents a material programming approach for designing 4D‐printed self‐shaping material systems based on biological role models. Plants have inspired numerous adaptive systems that move without using any operating energy; however, these systems are typically designed and fabricated in the form of simplified bilayers. This work introduces computational design methods for 4D‐printing bio‐inspired behaviors with compounded mechanisms. To emulate the anisotropic arrangement of motile plant structures, material systems are tailored at the mesoscale using extrusion‐based 3D‐printing. The methodology is demonstrated by transferring the principle of force generation by a twining plant ( Dioscorea bulbifera ) to the application of a self‐tightening splint. Through the tensioning of its stem helix, D. bulbifera exhibits a squeezing force on its support to provide stability against gravity. The functional strategies of D. bulbifera are abstracted and translated to customized 4D‐printed material systems. The squeezing forces of these bio‐inspired motion mechanisms are then evaluated. Finally, the function of self‐tightening is prototyped in a wrist‐forearm splint—a common orthotic device for alignment. The presented approach enables the transfer of novel and expanded biomimetic design strategies to 4D‐printed motion mechanisms, further opening the design space to new types of adaptive creations for wearable assistive technologies and beyond. Abstract : This paper presents a design and material programming approach for adaptive material systems through a case study of biomimetic design. The twining air potato ( Dioscorea bulbifera ) provides stability against gravity by tensioning its stem helix and generating a squeezing force. Based on D. bulbifera 's force generation, 4D‐printing is employed to produce adaptive wearable systems with passive, targeted shape changes.